CURRICULUM OF MASTERS OF MEDICINE: CHANGES IN THE DESIGN OF THE EDUCATIONAL PROCESS - Stechenko, Olena (Educological discourse, 2019)
Pedagogical design of the educational process is the main lever of improvement of specialist`s training in higher education. Special attention in this aspect should be paid to the curriculum of specialty, which defines the main vectors of the educational trajectory for education applicants, and provides opportunities for the implementation of the educational program`s competency-building tasks. The main differences between the curriculum of masters of medicine and the previous version - curriculum of specialists training in “General Medicine” are analyzed in the article. The main features of the structure of curricula for the physicians’ training in Poland are based on the example of the Warsaw Medical University and Collegium Medicum of the Jagiellonian University. On the basis of comparison and analysis conducted, the following changes in the design of masters of medicine curriculum in higher educational institutions (HEI) of Ukraine are predicted in accordance with the main trends in the European Higher Education Area. Increase of the classroom learning load in the general structure of credits up to 55% due to its growth at 2-5 courses is possible with the further design of curricula for physicians’ training. An increase in the number of class hours of production practice in the curriculum for the 4th year of studying – up to 82, for the 5th year – up to 102 hours without making changes in the number of credits is expedient. The volume of the lecture load is optimal to allocate from the largest one on the 1st year to the smallest – on 4th-5th years, with the simultaneous reduction of its quota in the structure of classroom hours. Taking into account the introduction of a united state qualification exam (USQE), increase in the number of credits for natural sciences up to 30% and simultaneous reduction in the number of credits for humanities (up to 2-3%) and to some degree – credits for professionally oriented disciplines (to 65-67%) can provide additional benefits to the design of curricula. The requirements of the higher education standard should be taken into account for adapting to the training of first-year students and improving of their training for both stages of external evaluation in the form of USQE, provided that a student-centered environment with better conditions is created.